2011
DOI: 10.1523/jneurosci.4162-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Intrinsic Membrane Properties and the Axon Initial Segment in a Mouse Model of Angelman Syndrome

Abstract: The axon initial segment (AIS) is the site of action potential initiation in neurons. Recent studies have demonstrated activity-dependent regulation of the AIS, including homeostatic changes in AIS length, membrane excitability, and the localization of voltage-gated Na + channels. The neurodevelopmental disorder Angelman syndrome (AS) is usually caused by the deletion of small portions of the maternal copy of chromosome 15, which includes the UBE3A gene. A mouse model of AS has been generated and these mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
139
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(148 citation statements)
references
References 36 publications
7
139
1
1
Order By: Relevance
“…An initial clue that these VGSC regulators may have distinct, nonredundant roles came from their strikingly dissimilar subcellular distributions within the same neuron. As expected by its localization to the axons of cerebellar granule neurons (23) and previous work in hippocampal neurons (31,32), FGF14 was concentrated in the axons of cultured hippocampal neurons (Fig. 1C, Left).…”
Section: Fgf13 and Fgf14 Are Differentially Localized Within Hippocampalsupporting
confidence: 86%
See 2 more Smart Citations
“…An initial clue that these VGSC regulators may have distinct, nonredundant roles came from their strikingly dissimilar subcellular distributions within the same neuron. As expected by its localization to the axons of cerebellar granule neurons (23) and previous work in hippocampal neurons (31,32), FGF14 was concentrated in the axons of cultured hippocampal neurons (Fig. 1C, Left).…”
Section: Fgf13 and Fgf14 Are Differentially Localized Within Hippocampalsupporting
confidence: 86%
“…Having thus validated the specificity of our Ab, we observed FGF13 localization in the hippocampus in brain slices, wherein the FGF13 signal is prominent in pyramidal neurons (Fig. 1B, Left), a cell population in which FGF14 is also highly expressed (31,32). As in cultured hippocampal neurons, FGF13 localized to axons (Fig.…”
Section: Fgf13 and Fgf14 Are Differentially Localized Within Hippocampalsupporting
confidence: 65%
See 1 more Smart Citation
“…Recent studies have identified several neuronal proteins that are mis-regulated in AS neurons, including CAMKII, RhoA guanine nucleotide exchange factor 5 (EPHEXIN5), activity-regulated cytoskeleton-associated protein (ARC), GAT1, α1-NAKA, NAV1.6, and ANKYRIN-G (8)(9)(10)(11)(12). Some of these proteins are thought to be direct substrates of UBE3A.…”
mentioning
confidence: 99%
“…AS mice have significant neural circuit defects, suggesting that in the absence of Ube3a there is a disruption of excitatory/ inhibitory balance in the brain (6,10,12,13,(17)(18)(19). In addition, AS mice display defects in learning and memory, motor coordination, locomotor activity (14,17,20,21), and an increased number of seizures when exposed to an audiogenic challenge (6,11).…”
mentioning
confidence: 99%